Adoption Level of Drum Seeder Technology in Rice cultivation - P.Venkata Rao; S.Neelaveni; P.B Pradeep Kumar; P.Punna Rao (Journal of Agricultural Extension Management, 2015)
This study was conducted with an objective of studying the adoption level of drum seeder technology in north coastal zone of Andhra Pradesh. Ex-post facto research design was used with a sample size of 100 farmers adopting drum seeder technology in rice cultivation. Majority of the farmers had medium level of adoption. The correlation analysis revealed that extension contact, achievement motivation, innovativeness, information seeking behavior, education, irrigation facility and risk taking ability were significantly related to the adoption of drum seeder technology. Practice wise analysis revealed that 41.00 per cent of the farmers had partial adoption and 35 per cent had full adoption. There were 24.00 per cent of the farmers who did not adopt certain drum seeder technology practices